The Influence of Differentiated Learning Models on Student Achievement in Islamic Religious Education at SMP Negeri 11 Palu - Ifada, Daniati; Rustina; Patanggu, Irawanhadi (Al-Tawjih: Jurnal Pendidikan Islam, 2025)
Learning is a crucial component of the educational system. Educational quality cannot be optimized if the learning process is low in quality. Therefore, continuous improvement in instructional quality is essential to achieve high-quality education. Based on this premise, this study aims to examine whether the Differentiated Learning Model has a significant effect on students’ learning outcomes in Islamic Religious Education (IRE) at SMP Negeri 11 Palu. This research employed a quantitative experimental approach. Data were collected through achievement tests and non-test instruments, including observation sheets and documentation. The results indicate that the differentiated learning model has a significant effect on students’ learning outcomes. Statistical analysis shows that the mean posttest score of the experimental group was significantly higher than that of the control group. The t-test results reveal a significance value (p-value) of 0.001 < 0.05, with t_calculated > t_table, indicating a significant difference in learning outcomes between the two groups. Furthermore, the analysis of covariance (ANCOVA) supports these findings, with a p-value < 0.001, demonstrating that the differentiated learning model significantly influences students’ learning outcomes even after controlling for pretest scores. Overall, differentiated learning positively impacts students’ engagement, motivation, and comprehension of learning materials. Students become more actively involved in the learning process because the instruction is tailored to their learning styles, interests, and readiness levels. The implications of this research reinforce Tomlinson’s theory, which asserts that differentiated instruction is effective at accommodating student diversity in interests, readiness, and learning styles. Consequently, these findings contribute to the development of modern learning theories that emphasize the importance of adaptive instruction responsive to individual student characteristics.